Climate change is associated with increased allocation to potential outcrossing in a common mixed mating species. Issue 7 (28th June 2022) - Austin, Matthew W.; Cole, Piper O.; Olsen, Kenneth M.; Smith, Adam B.
Abstract: Premise: Although the balance between cross‐ and self‐fertilization is driven by the environment, no long‐term study has documented whether anthropogenic climate change is affecting reproductive strategy allocation in species with mixed mating systems. Here, we test whether the common blue violet ( Viola sororia ; Violaceae) has altered relative allocation to the production of potentially outcrossing flowers as the climate has changed throughout the 20th century. Methods: Using herbarium records spanning from 1875 to 2015 from the central United States, we quantified production of obligately selfing cleistogamous (CL) flowers and potentially outcrossing chasmogamous (CH) flowers by V. sororia, coupled these records with historic temperature and precipitation data, and tested whether changes to the proportion of CL flowers correlate with temporal climate trends. Results: We find that V. sororia progressively produced lower proportions of CL flowers across the past century and in environments with lower mean annual temperature and higher total annual precipitation. We also find that both CL and CH flower phenology has advanced across this time period. Conclusions: Our results suggest that V. sororia has responded to lower temperatures and greater water availability by shifting reproductive strategy allocation away from selfing and toward potential outcrossing. This provides the first long‐term study of how climate change may affect relative allocation to potential outcrossing in species with mixed mating systems. By revealing that CL flowering is associated with low water availability and high temperature, our results suggest the production of obligately selfing flowers is favored in water limited environments.